THE SYSTEM OF SPIRITUAL AND MORAL VALUES OF THE UZBEK PEOPLE AND THEIR IMPACT ON LANGUAGE CULTURE - Mustafayeva Sarvinoz Suyunovna (Bright Mind Publishing, 2026)
This article examines the system of spiritual and moral values of the Uzbek people and their influence on language culture from socio-philosophical and axiological perspectives. The study explores the historical formation of national values, their role in spiritual education, and the mechanisms of their manifestation in language culture. Language culture is interpreted as a socio-cultural phenomenon that expresses and transmits values such as respect, modesty, responsibility for speech, and norms of communication. The paper substantiates the idea that language culture serves as an indicator of spiritual maturity and a factor in strengthening national identity. Particular attention is paid to the interaction between national values and language culture in the context of globalization.
Keywords: Spiritual values, moral system, language culture, spiritual education, national identity, speech etiquette, axiology, social consciousness.